CCDC138 overexpression predicts poor prognosis and highlights ciliopathy-linked mechanisms in uterine corpus endometrial carcinoma - Wang, Aiping; Yang, Fang; Zhang, Chunhua; Li, Shi; Fu, Han (Frontiers in Molecular Biosciences, 2025)
IntroductionUterine corpus endometrial carcinoma (UCEC) is a prevalent malignancy of the female reproductive system with increasing incidence, necessitating the identification of molecular mechanisms and biomarkers. While coiled-coil domain-containing protein 138 (CCDC138) is implicated in ciliopathies and cancer, its role in UCEC remains underexplored.MethodsWe integrated transcriptomic and proteomic data from the Cancer Genome Atlas (TCGA), Clinical Proteomic Tumor Analysis Consortium (CPTAC), and Genotype-Tissue Expression (GTEx). Bioinformatics approaches, including weighted gene co-expression network analysis (WGCNA), singlesample gene set enrichment analysis (ssGSEA), machine learning, and survival analysis, were employed to assess CCDC138 expression and its functional relevance in UCEC. In vitro experiments involved CCDC138 knockdown, followed by CCK8 and EdU assays and qPCR for mTOR, S6K1, and p21 expression.ResultsCCDC138 was significantly overexpressed at mRNA and protein levels in UCEC and correlated with poor overall survival. ssGSEA revealed associations with oncogenic pathways, including mTOR, p53/Rb, and MYC/MYCN. High CCDC138 expression was linked to reduced stromal and immune scores, indicating altered immune cell infiltration and tumor microenvironment. Drug sensitivity analysis showed increased responsiveness to chemotherapeutic agents like 5-fluorouracil and alpelisib in high-CCDC138 tumors. Protein-protein interaction analysis identified interactions with DCTN2 and CEP72. In vitro, CCDC138 knockdown reduced cell proliferation and downregulated mTOR, S6K1, and p21 mRNA expression.DiscussionThese findings underscore CCDC138’s role in UCEC progression, immune modulation, and therapeutic responsiveness, highlighting its potential as a prognostic biomarker and therapeutic target. Its shared relevance in UCEC and ciliopathies suggests broader implications for targeted therapies.